2011
DOI: 10.1074/jbc.m111.224212
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Impairs Angiogenesis through Inhibition of MicroRNA-10b

Abstract: Heparin, which has been used as an anticoagulant drug for decades, inhibits angiogenesis, whereas thrombin promotes tumor-associated angiogenesis. However, the mechanisms underlying the regulation of angiogenesis by heparin and thrombin are not well understood. Here, we show that microRNA-10b (miR-10b) is down-regulated by heparin and up-regulated by thrombin in human microvascular endothelial cells (HMEC-1). Overexpression of miR-10b induces HMEC-1 cell migration, tube formation, and angiogenesis, and downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 57 publications
(79 reference statements)
4
54
0
1
Order By: Relevance
“…In fact, suppression of miR-10b and miR-196b led to significant defects in tube number, length, and mobilization in human and murine endothelial cells (Fig. 5) in agreement with a recent observation showing that miR-10b regulates HOXD10 in microvessels (35). HOXD10 has been showed to suppress angiogenesis (37).…”
Section: Vegfr2supporting
confidence: 75%
“…In fact, suppression of miR-10b and miR-196b led to significant defects in tube number, length, and mobilization in human and murine endothelial cells (Fig. 5) in agreement with a recent observation showing that miR-10b regulates HOXD10 in microvessels (35). HOXD10 has been showed to suppress angiogenesis (37).…”
Section: Vegfr2supporting
confidence: 75%
“…Contrary to being increased in human pancreatic adenocarcinomas and glioblastoma multiforme (Ciafre et al, 2005; Bloomston et al, 2007), miR-10b has been found to be decreased in breast cancer tissues (Ma et al, 2007). MiR-10b levels have been reported to be repressed by heparin; however, they are increased by thrombin in human microvascular endothelial cells (Shen et al, 2011). In future studies, the function of miR-10a in angiogenesis should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-10b has recently been suggested to regulate angiogenesis in human microvascular endothelial cells, where miR-10b overexpression promoted endothelial cell migration and tube formation. 35 These findings raise the possibility that this microRNA may also regulate proangiogenic effects in CD34 ϩ mononuclear cells; this needs to be further evaluated in future studies. However, miR-10b was substantially higher expressed in CD34 ϩ CD14 ϩ compared with CD34 ϩ CD14 Ϫ mononuclear cells that had a rather similar proangiogenic capacity in the present study, which would suggest that miR-10b is not a major regulator of proangiogenic effects of CD34 ϩ mononuclear cells.…”
Section: Org Frommentioning
confidence: 99%